MENINGKATKAN KEMAMPUAN MENGENAL LIMA HURUF VOKALMELALUI MEDIA BOLA HURUF PADA ANAK USIA 5-6 TAHUN KELOMPOK B DI TKIT JUARA TANJUNG TIRAM KABUPATEN BATU BARA - Nurhikmah Pohan, Nilam Fauzi (Pusdikra Publishing, 2020)
This research is motivated by the difficulties of children aged 5-6 years at TKIT Champion Tanjung Tiram in recognizing five vowels, namely children often find it difficult to mention and distinguish vowels such as